Creating alliesthesia in cool environments using personal comfort systems. (1st February 2022) - He, Yingdong; Parkinson, Thomas; Arens, Edward; Zhang, Hui; Li, Nianping; Peng, Jinqing; Elson, John; Maranville, Clay
Abstract: Personal Comfort Systems (PCS) promise to reduce the energy needed to condition indoor environments, while also enhancing their occupants' thermal pleasure. To explore these potentials in heating conditions, we compared the effectiveness of PCS heating various portions of the occupant against the normal Air Conditioning (AC) practice of warming the room volume. Twenty subjects experienced three modes of heating (AC only, AC together with PCS, and PCS only) at three initial room air temperatures (14, 16, and 18 °C) and were given some control options throughout the testing. Skin temperatures, thermal pleasantness, and thermal sensation votes were recorded during the exposures. The PCS heating was more effective than AC control at alleviating occupant discomfort. With PCS present, the three initial room temperatures produced equivalent positive perceptions of thermal pleasantness and sensation. Providing occupants with AC control did not influence this result. AC alone did not produce appreciable alliesthesia due to its slow rate of changing the room temperature. In contrast, PCS produced an immediate pleasantness experience with its faster-acting conductive and radiative heating spread non-uniformly across the body. Whole-body thermal pleasantness closely followed the pleasantness of local body parts experiencing thermal stimuli. These temporal and spatial characteristics give PCS a significant advantage in generating thermal pleasure over traditional AC systems. Highlights: PCS provided fast and intense heating that was non-uniformly distributed across the body. PCS first triggered temporal alliesthesia and then spatial alliesthesia. Whole-body thermal pleasantness followed heated local body sites' pleasantness. AC systems are unlikely to generate thermal pleasure due to their slow heating. The role of the ambient temperature on pleasantness was much reduced with PCS heating.